ANALISA DAN PERKEMBANGAN KEBIJAKAN HUKUM LINGKUNGAN DALAM UPAYA PENANGANAN KARHUTLA - Rohmah, Miftakhur; Ryzkyana, Cyntia Finda (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2021)
Forest fires are considered to be local and global concern as one of the environmental problems because they brings such a big impact for ecosystem and global warming. In Indonesia, Forest fires or Karhutla often occures during dry seasons and its impacting health problems, forcing the whole city to close educational infrastructure even the smoke effects reaching neighboring countries. The law enforcement for environmental issues is still difficult because of lack of law and the stake-holders aren't intregating with each other.